Chronology and documentary handbook of the State of Alabama. - Trover, Ellen Lloyd (Chronologies and documentary handbooks of the States, 1972)
Includes a chronology of historical events in Alabama, a directory of prominent citizens, an outline of the state constitution, and selected documents important in Alabama's past.